SPE Annual Technical Conference and Exhibition 1997
DOI: 10.2118/38620-ms
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Effect of Formation Water on Fracture Fluid Cleanup Through Field Testing in the East Texas Cotton Valley

Abstract: A field study in east Texas showed that formation water production influences polymer recovery from hydraulic fractures. This study was conducted on 10 wells located in the Cotton Valley Taylor formation. A typical fracture stimulation design included between 9,000 to 14,000 bbl of zirconium crosslinked guar gel. Detailed chemical analysis of flowback samples was used to identify the effect of formation water on polymer recovery. Polymer and chloride concentrations were measured. Water produced during flowback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…As stated by Willberg et al (1997), only 30-45% of the guar-based polymer fracturing fluid can be returned back from the well during flow back period. Laboratory experiments by Willberg et al (1997) have shown that unbroken residues from polymer-base fluids can indeed plug the pores of the proppant pack.…”
Section: Introductionmentioning
confidence: 98%
“…As stated by Willberg et al (1997), only 30-45% of the guar-based polymer fracturing fluid can be returned back from the well during flow back period. Laboratory experiments by Willberg et al (1997) have shown that unbroken residues from polymer-base fluids can indeed plug the pores of the proppant pack.…”
Section: Introductionmentioning
confidence: 98%
“…Tight reservoirs with very low permeability can have considerably high capillary forces requiring enough viscous forces across the fracture face to displace the entrapped fracturing fluids (Holditch 1979). Also, formation water production can hinder the fracture cleanup operation considerably due to viscous fingering; this will weaken the effects of other factors in enhancing the cleanup (Willberg et al 1997;Mahadevan and Sharma 2003). Analyzing the PBU data of the three wells or their offsets, the effect of reservoir characteristics on the flowback analyses results can be deduced and presented below.…”
Section: Factors Affecting Cleanup Performancementioning
confidence: 99%
“…Willberg et al (1997Willberg et al ( , 1998 showed that formation water production can limit the effective polymer recovery during cleanup. In their study, they compared the laboratory testing results on recovered flowback samples for 10 wells producing formation water in one of East Texas fields to neighboring fields with no formation water production issues.…”
Section: Figure 6c-ratio Between Peak 1 and Peak 2 Heights For Well-cmentioning
confidence: 99%
“…The conductivity, in turn, will depend on the fluid-loss, 34,35 rock dissolution, 36 and the damage associated with the treatment fluids. 1,6,37 To control leak-off, the industry has been using emulsions and gelled acids. 34,38 The emulsified acid is highly retarded and will help to achieve differential etched pattern deeper in the fracture.…”
Section: (Iii) Acid Fracturingmentioning
confidence: 99%